Dynamics of Social and Ecological Adaptation in Multi-Level Governance: A Community Social Perspective in Environmental Management - Nur Mawaddah (Pemuda Peduli Publikasi Insan Ilmiah, 2024)
Purpose: This study examines the dynamics of social and ecological adaptation in multi-level governance, emphasizing the role of community perspectives in environmental management. Subjects and Methods: A quantitative, descriptive, and correlational design was applied using a cross-sectional survey of 200 households in coastal, upland, and urban areas of South Sulawesi. Data were collected through structured questionnaires and analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis. Results: The findings reveal that governance effectiveness, community participation, and trust in institutions are positively associated with adaptation capacity. Community participation emerges as the strongest predictor, followed by trust and governance effectiveness. These results highlight the importance of social engagement and relational dynamics alongside institutional structures. Regional variations further indicate that adaptation is shaped by context-specific environmental and social conditions. Conclusions: Adaptive capacity is strengthened through integrated governance approaches that combine institutional effectiveness, active community participation, and trust-building strategies.